Attitude Towards Telemedicine Among Women of Childbearing Age With Fibroid Tumor Attending Aminu Kano Teaching Hospital, Kano State - Makinde, Oluwayemisi Adefunke; Abdullah, Abdulsalam (NIU Journal of Social Sciences; Vol 10 No 4 (2024): NIU Journal of Social Sciences, Vol. 10 No. 4 December 2024, 2024)
Telemedicine gains traction, particularly following the COVID-19 pandemic, its potential to enhance healthcare access for women with fibroids remains a critical area for investigation. This study aims to assess the attitudes of women of childbearing age towards telemedicine at Aminu Kano Teaching Hospital, Kano State, Nigeria. A cross-sectional research design was employed to examine the attitudes of 197 women towards telemedicine for managing fibroid tumors. Participants were selected through an availability sampling method, and data were collected via a structured questionnaire. The instrument was validated and assessed using Cronbach's Alpha, revealing a reliability coefficient of 0.82. Data analysis involved descriptive statistics and one sampled t-test at a significance level of 0.05. The study revealed that the majority of respondents were aged between 36-45 years (43.30%), predominantly married (69.71%), and had varied educational backgrounds. The analysis indicated a mean attitude score of 2.1866, falling below the neutral mean of 2.5, with a t-test indicating no statistically significant attitude towards telemedicine (p = 0.1001). This suggests that the participants do not exhibit a significant inclination towards the use of telemedicine for managing fibroid tumors. To foster a more positive attitude towards telemedicine among women with fibroid tumors, it is recommended to develop telemedicine platforms that support local languages, implement comprehensive cultural competency training for healthcare providers, and establish telemedicine support centers within the local health system to provide accessible consultations. Keywords: Telemedicine, Uterine Fibroids, Women’s Health, Attitude, Kano State